Implementing of the offline setup correction protocol in pelvic radiotherapy - Kasabašić, Mladen (Radiology and oncology (Ljubljana), 2007)
Background. Patient positioning errors in pelvic radiotherapy at Department ofOncology and Radiotherapy in Osijek are explored in order to establish the offline setup correction protocol and determine the safely margins. Material and methods. Film portal imaging is used during the whole treatment in order to find patient positioning errors. Eleven patients are included in the study and 420 images are analyzed. Setup errors are found by measuring distances between the center of the field and bony landmarks. Systematic and random errors are analyzed. Results. Safety margins that should be employed at our department are 11 mm, 13 mm and 14 mm in mediolateral, craniocaudal and anteroposterior direction, respectively. Time trend is found only in an aged, obese patient with a hip problem. No action level offline setup protocol was employed by taking and averaging first four images in mediolateral and craniocaudal and 5 images in anteroposterior direction. Conclusions. Since time tvend is found only in a patient who was hard to position because of his age, obesity and the hip problem, we decided that such patients are to be positioned without a bellyboard and in supine position. Time trends are not found in all of the other patients so we employed the offline setup error protocol by averaging setup errors from the first few consecutive images. Safety margins that will ensure 90% probability of depositing at least 95 % ofthe prescribed dose in the target are calculated. Safety margins and number of images that should be taken showed that the most inaccurate positioning wasin the anteroposterior direction.
Keywords: Maternica, novotvorbe; medenica; Methods; onkologija; radioterapija; Radioterapija, doziranje; Radiotherapy; Radiotherapy Dosage; Rectal Neoplasms; Rektalne novotvorbe; therapy; Uterine Neoplasms; zdravljenje